Low circulating levels of neuregulin 4 as a potential biomarker associated with the severity and prognosis of obesity-related metabolic diseases: a systematic review - Khanyisani Ziqubu; Phiwayinkosi V. Dludla; Sinenhlanhla X.H. Mthembu; Bongani Nkambule; Sithandiwe E. Mazibuko-Mbeje (Adipocyte)
Background Neuregulin 4 (Nrg4) is a brown adipose tissue-derived adipokine that greatly affects systemic metabolism and improves metabolic derangements. Although abnormal circulating levels of Nrg4 are common in obesity, it remains elusive whether low or elevated levels of this batokine are associated with the onset of metabolic diseases.Aim To assess Nrg4 levels and its role as a feasible biomarker to predict the severity of obesity, gestational diabetes mellitus (GDM), type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases (CVD).Methods A search for relevant studies was performed systematically using prominent search engines, including PubMed, Google Scholar, and Embase, by following PRISMA guidelines.Results Ample clinical evidence reported low serum/plasma levels of Nrg4 in obesity and these were inversely proportional to the indices of metabolic syndrome, including body mass index, waist circumference, triglycerides, fasting plasma glucose, and homoeostatic model assessment for insulin resistance as well as high-sensitivity C-reactive protein. Low circulating Nrg4 levels may aid in the prediction of morbid obesity, and subsequent GDM, T2DM, NAFLD, and CVD.Conclusion Current clinical evidence emphasizes that the circulating levels of Nrg4 are decreased in morbid obesity, and it also highlights that Nrg4 May serve as a potential prognostic biomarker for obesity-related metabolic diseases.